PENGARUH PAJAK AIR PERMUKAAN TERHADAP PENDAPATANASLI DAERAH DIBAPENDA KABUPATEN SUKABUMI PERIODE 2018-2022 - Fuji, Fuji Nurlaela; Euis Hernawati (JEBS (Journal of Economic and Business Student), 2024)
This research aims to find out the influence of surface water tax on local revenue in Bapenda in Sukabumi I Regency for the 2018-2022 period. The method used in this research is descriptive quantitative by collecting data from field studies, library and website studies. The sample used in this research is data on surface water tax revenues and local original income revenues in 2018-2022. Based on the research results, it can be found that the results of surface water tax revenues and local original income have a very strong relationship, with local original income of 0.030 and an influence of 83.5% while the remaining 16.5% is influenced by other variables outside this regression equation or variables not studied. The results of the research show that the tax collection process has been carried out well, but there are still obstacles experienced in the collection process, namely the lack of knowledge of taxpayers regarding the surface water tax payment process, the existence of arrears in tax payments. The efforts made to overcome these obstacles are by following developments in social media, and holding a tax whitening program every year, to make it easier to pay off arrears.